Biopsychosocial risk factors for pain in early phases of pediatric cancer treatment - Klages, Kimberly L.; James, Ryan N.; Kain, Zeev N.; Phipps, Sean; Alberts, Nicole M.; Fortier, Michelle A. (Frontiers in Psychology, 2025)
IntroductionCancer pain remains a significant burden among children with cancer, and many patients experience pain starting around the time of diagnosis and throughout the course of treatment. A biopsychosocial treatment approach has been recommended to improve pain management in this population; however, specific psychosocial factors that contribute to pain in the early phases of pediatric cancer treatment have yet to be identified. The purpose of this study was to explore the biopsychosocial factors associated with pain experiences during the early phases of pediatric cancer treatment, with the goal of identifying children who may be at the highest risk for pain to inform future intervention and prevention efforts.MethodsData were collected from 203 children with cancer (M = 12.3 years of age, 53.2% male, 41.4% White, 26.6% Latino) and their primary caregiver within the first several weeks of treatment (M = 10 weeks). Children completed self-report questionnaires and caregivers completed self- and parent-proxy questionnaires at baseline. Cancer-related data, including diagnosis and date of diagnosis, were abstracted from the child's electronic medical record. Multiple regression analysis was used to examine associations between biopsychosocial risk factors, pain intensity, and pain interference.ResultsOlder age, female gender, and elevated depressive symptoms, fatigue, and child self-reported pain catastrophizing were significantly associated with increased pain intensity. Additionally, lower annual income, decreased physical functioning, and greater fatigue, child pain catastrophizing, and parent stress were significantly associated with increased pain interference.DiscussionFindings underscore the importance of utilizing a comprehensive biopsychosocial approach to pain assessment and management in pediatric oncology. This approach highlights the need for targeted interventions that address not only the physical aspects of pain but also the psychological and social contexts of patients, ensuring a more holistic and effective treatment strategy.